Unveiling the photophysical properties of 3-acyl-6-amino-4-quinolones and their use as proton probes. (November 2022) - Costa, Amanda R.P.; de Andrade, Karine N.; Moreira, Micaeli L.S.; Oliveira, Vanessa G.; Carneiro, José W.M.; Boechat, Fernanda da C.S.; de Souza, Maria C.B.V.; Fiorot, Rodolfo G.; Teixeira, Rodolfo I.; de Lucas, Nanci C.; Batalha, Pedro N.
Abstract: 4-quinolone derivatives are widely explored in Medicinal Chemistry for the development of drug candidates for the treatment of different pathologies. However, their optical properties remain underexploited. In this work, the photophysical properties of a family of 3-acyl-6-amino-4-quinolone derivatives were investigated, highlighting their optical behaviour towards acids. Although the substances did not show significant solvatochromism, in the presence of trifluoroacetic acid alterations were observed in their photophysical profile, especially regarding their emissive response. The ester derivatives 1-alkyl-6-amino-4-oxo-1, 4-dihydroquinoline-3-carboxylate exhibit a more significant increase in intensity (>2 times-fold) and a considerable redshift (∼90 nm), leading to emission colour change from blue to green in acidic condition. The changes were highly sensitive, detecting proton concentrations as low as 10 μM in MeCN. This molecular system was studied by NMR and DFT calculations that show the 1, 3-diketone as the preferred protonation site. The establishment of an intramolecular hydrogen bond between the ketone and carbethoxy groups leads to LUMO stabilization and a practically coplanar protonated structure, favouring fluorescence. Notably, the presence of intra- or intermolecular hydrogen bonding has a major impact on their sensing behaviour, making the changes for the acid and amide derivates require a 1000-fold higher concentration of TFA than the ester analogue. The calculated thermodynamic values for the acid equilibrium show that the established hydrogen bond in the neutral species reduces the basicity of these quinolones, agreeing with the experimentally calculated p K values of 4.53, 2.56 and 1.75 for the ester, amide and acid derivatives respectively. Finally, the presence of the amino substituent, linked to the C-6 of the 4-quinolone structure, was shown to be important for the optical profiles and sensitivity observed. Graphical abstract: Image 1 Highlights: 3-Acyl-6-amino-4-quinolones as proton probes. Sensitivity for proton detection in the range of 10 μM. Green emission upon acid addition. Properties highly dependent of intramolecular and intermolecular hydrogen bonding.